Gender Peculiarity of Compound Words in Describing the Appearance and Character of a Person in English and Uzbek Languages - Hotamova Iroda Ibrohimovna (Academia One, 2023)
The current article is devoted to find new approaches of comparing and classifying the compounds which describe human appearance and character in English and Uzbek languages. As we know, there are not enough manuals, which compared the Uzbek and the English languages. The novelty of the work is that in the work one can you can see a tabulated sample of English and Uzbek compound words used to describe a person's appearance. The gender factor in the appearance and character of the person in compound words acquires particular significance in English and Uzbek languages. Gender marked difficult words describing the character and appearance of the man in fiction, is considered moral, behavioral, on the basis of values: good - bad, the good and the evil, beautifully - ugly. The analysis revealed gender marked difficult words describing the character and appearance of the man in the positive and negative evaluation plan.
Keywords: classification of compound words; gender; tabulated of compounds